2001
DOI: 10.1016/s0735-1097(01)01540-6
|View full text |Cite
|
Sign up to set email alerts
|

Initial energy setting, outcome and efficiency in direct current cardioversion of atrial fibrillation and flutter

Abstract: An initial energy setting of > or =360 J can achieve cardioversion of AF more efficiently in patients than traditional protocols, particularly with AF of longer duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 15 publications
0
47
2
Order By: Relevance
“…With 360 J of shock, we achieved an 84% success rate. We did not find, as Gallagaher, et al 23) did in their study, that AF duration affects the energy requirement. Thus, based on their and our results, it is reasonable to start with a 200 J shock, as this level of energy is capable of achieving a reasonable AF conversion success rate, supporting the recent recommendations for electrical cardioversion of atrial fibrillation.…”
Section: )contrasting
confidence: 75%
See 1 more Smart Citation
“…With 360 J of shock, we achieved an 84% success rate. We did not find, as Gallagaher, et al 23) did in their study, that AF duration affects the energy requirement. Thus, based on their and our results, it is reasonable to start with a 200 J shock, as this level of energy is capable of achieving a reasonable AF conversion success rate, supporting the recent recommendations for electrical cardioversion of atrial fibrillation.…”
Section: )contrasting
confidence: 75%
“…20,21) Other studies have suggested that 360 J, or 200 J at a minimun, should be used as an initial energy level for elective cardioversion of persistent AF. 22,23) Gallagher, et al 23) even reported that, for patients with AF for more than 30 days, shocks of < 200 J simply were a waste of time. They observed that in patients with AF for > 180 days, an initial setting of ≥ 300 J reduced the total energy used but achieved a modest success rate of 56%.…”
Section: )mentioning
confidence: 99%
“…70,71 Transthoracic direct-current cardioversion, under short-lasting sedation, is the quickest and most effective method to recover sinus rhythm in patients with flutter, with a lower energy delivery and higher success rate than in AF. 72,73 In 50-80 % of cases flutter interruption can be achieved by atrial pacing above the flutter rate through a transvenous catheter, through epicardial electrodes placed during cardiac surgery 8 or by programming fast atrial rates in patients with atrial or dual-chamber pacemakers. 74 Pacing runs of 20-30 s are started at a rate 10 bpm higher than flutter, increasing in 10 bpm steps up to 400 bpm or until flutter is interrupted and sinus (or paced) atrial rhythm is established (see Figure 6).…”
Section: 69mentioning
confidence: 99%
“…Electrical CV success rates vary from 75 to 93%. They are inversely related to the AF duration, chest wall impedance, and left atrial size [48][49][50][51][52]. Indeed, success rates vary according to the point in time that success is defined.…”
Section: Electrical Cardioversion Of Af/afl In Edmentioning
confidence: 99%